Causes of school dropouts from the point of view of parents - Hussein, Ola Ali; Al-Halabiyah, Fadwa Abdullah (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the reasons for dropping out of school from the point view of parents, which the study identified in two areas: the school environment and the financial and living conditions of the family. The study used the descriptive approach by designing a questionnaire. The sample consisted of (217) parents of student at secondary level in the non-governmental schools in Bethany and Abu Dis. The results indicated that the area of ​​school environment is high, while the financial and living conditions of the family are medium. The results of the study also indicated that there are statistically significant differences in the reasons for dropping out of schools from the parents’ point of view due to variables of educational level and family income level. While, there are no statistically significant differences due to variables parental status (father, mother) and marital status. The study recommends the importance of implementing awareness and guidance programs for teachers and school administrators on the problem of dropout and understand the psychological, social and academic needs of students, especially the academic, as well as the importance of the implementation of individual case studies on the school environment and its relationship to school dropout.